Hands-on mathematics for deep learning : build a solid mathematical foundation for training efficient deep neural networks - Dawani, Jay (Packt Publishing, 2020)
The main aim of this book is to make the advanced mathematical background accessible to someone with a programming background. This book will equip the readers with not only deep learning architectures but the mathematics behind them. With this book, you will understand the relevant mathematics that goes behind building deep learning models.